Using Quantum Coherence to Enhance Gain in Atomic Physics - Jha, Pankaj K. (Coherent phenomena, 2013)
Quantum coherence and interference effects in atomic and molecular physics have been extensively studied because of intriguing counterintuitive physics and potential important applications. Here we present one such application, i.e. using quantum coherence to generate and enhance gain in the extreme ultra-violet (XUV)(@58.4nm in Helium) and infra-red (@794.76nm in Rubidium) regimes of electromagnetic radiation. We show that using moderate external coherent drive, a substantial enhancement in the output energy on the lasing transition can be achieved under optimal conditions. We also discuss the role of coherence. The present paper is intended to be pedagogical on this subject of coherence-enhanced lasing.